RUANG PEMBERDAYAAN KAUM IBU MUARA ANGKE SEBAGAI TEMPAT KETIGA - Joshua Ervin Novaldi; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Jakarta as the capital of the country has changed for many years. Every change that occurs is influenced by problems that are in each region. This unites the uniqueness of each region by solving different problems. From this uniqueness, it makes every region in Jakarta has its sector, such as offices, housing, industry, and others. Although there are many sectors in Jakarta with the same function, the problems that occur are not necessarily the same that depends on the people in them. Coupled with the distribution of people coming and going to Jakarta which is quite large, adding to the variable of each problem area is solved. The Muara Angke region, Penjaringan, Pluit is a fishing and housing industry area that is visited by many visitors a day. The majority of the Muara Angke community are fishermen, but because of the times, many have left the fishing work and turned to office workers. With the level of which is relatively low, office work is difficult. The main objective of solving problems in each region is to increase the income of the community. Muara Angke with its fishing and marine products industry has not been maximized to make its people prosperous because there are still many fishermen who depend on boat charterers who make their income reduced. From the results of studies of empowerment of mothers in Muara Angke can maximize the natural resources obtained from the community. Placement of mothers becomes the midpoint of solving the Muara Angke problem through the third room is expected to be able to boost the quality of life of the people of Muara Angke with the area of gathering and working. The establishment of this third space is supported and based on PermenKP law number 28 in 2016, PermenKP number 51 in 2016, KepmenKP number 67 in 2016 which contains gender-responsive activities. Keywords: Gender; Life Quality; Public Space; Sea Resources AbstrakJakarta sebagai ibu kota negara selama bertahun-tahun banyak mengalami perubahan. Setiap perubahan dipengaruhi oleh masalah yang ada di setiap wilayahnya. Hal ini memunculkan keunikan setiap wilayah dengan penyelesaian masalah yang berbeda-beda. Keunikan ini menjadikan setiap wilayah mempunyai sektor masing-masing seperti wilayah perkantoran, perumahan, industri, dan lain-lain. Walaupun banyak sektor di Jakarta dengan fungsi yang sama, masalah yang terjadi belum tentu sama, bergantung kepada masyarakat di dalamnya. Ditambah dengan persebaran penduduk datang dan pergi Jakarta yang terbilang cukup besar, menambah variabel dari setiap masalah wilayah yang diselesaikan. Muara Angke, Penjaringan, Pluit merupakan wilayah industri perikanan dan perumahan yang didatangi banyak pengunjung perharinya. Mayoritas nelayan, akan tetapi perkembangan zaman merubah pekerjaan nelayan dan beralih ke pekerja kantoran, namun pekerjaanan ini menjadi hal sulit, mengingat tingkat pendidikan di Muara Angke terbilang rendah. Tujuan utama dari penyelesaian masalah setiap wilayah adalah untuk peningkatan pendapatan masyarakatnya. Muara Angke dengan industri perikanan dan hasil lautnya belum maksimal untuk membuat masyarakatnya hidup sejahtera karena masih banyak nelayan yang bergantung kepada penyewa kapal yang membuat pendapatan mereka berkurang. Pemberdayaan kaum ibu di Muara Angke bisa memaksimalkan sumber daya alam yang didapat. Penempatan kaum ibu menjadi titik tengah dari penyelesaian masalah Muara Angke melalui ruang ketiga, diharapkan dapat mendongkrak kualitas hidup masyarakat dengan adanya area berkumpul dan bekerja. Pembentukan ruang ketiga ini didukung dan didasarkan oleh undang-undang PermenKP nomor 28 tahun 2016, PermenKP nomor 51 tahun 2016, KepmenKP nomor 67 tahun 2016 yang berisikan tentang kegiatan responsif gender.